Sexual dysfunction: an interdisciplinary problem of classical gynecology - Natalia M. Podzolkova; Liliana V. Sumyatina (IP Berlin A.V., 2023)
Sexual dysfunction in women is a complex interdisciplinary medical problem that remains beyond the attention of an obstetrician-gynecologist and negatively affects a woman's quality of life and well-being. The article presents data on prospects for using herbal agents based on the chasteberry fruit extract (Vitex agnus-castus, chaste tree) in women with sexual dysfunction.